Perio J 2019
DOI: 10.26810/perioj.2019.a3
|View full text |Cite
|
Sign up to set email alerts
|

Is Entamoeba Gingivalis a Risk Factor for Periodontal Diseases? A Case-Control Study

Abstract: Background: Entamoeba gingivalis was the first commensal parasite detected in the oral cavity of humans, and a high incidence has been reported in patients with poor oral hygiene. The current study aimed to investigate the association of Entamoeba gingivalis with gingivitis and periodontitis among Egyptian subjects. Methods: A total of 120 plaque samples were collected for this case-control study and were divided as follows: 40 plaque samples from gingivitis patients (group 1), 40 from stage II grade A and B p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…This may explain the signi cantly higher number within samples isolated from the diseased cases, taking into consideration that all the enrolled subjects were immunocompetent. This intense colonization within immunocompetent subjects was previously reported in other work published by Hassan et al (2019).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This may explain the signi cantly higher number within samples isolated from the diseased cases, taking into consideration that all the enrolled subjects were immunocompetent. This intense colonization within immunocompetent subjects was previously reported in other work published by Hassan et al (2019).…”
Section: Discussionsupporting
confidence: 86%
“…Entamoeba gingivalis parasitic trophozoites were frequently detected in oral cavities, yet the association of periodontitis with this protozoan is still debatable, uctuating from complete accusation to intense rejection of such an association (Bonner et al, 2018). Very few published scienti c studies relied on the speci c parasitological parameters to identify the oral protozoan microscopically, yet nearly all of them con rmed its 100% occurrence within progressive periodontal pockets and from 0 to 26% within healthy periodontal sites (Fisher, 1927;Hinshaw and Simonton, 1928;Wantland and Wantland, 1960;Wantland and Lauer, 1970;Gottlieb and Miller, 1971;Keyes and Rams, 1983;Lange, 1984;Linke et al, 1989 andHassan et al, 2019). Unfortunately, for unknown reasons, all these articles neglected the difference in morphological characteristics between the detected trophozoites among the diseased and healthy periodontal sites, except Hassan et al (2019) in which detailed information was reported, yet not speci cally with the different conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess reproducibility of these results, a limited number of studies were found (34,36,43,53,54). The comparisons were further complicated by the reliance of a majority of the previous studies on microscopic detection methods (examination of wet mounts or permanent stained smears) (35,(37)(38)(39)(40)(41). In the current study, a significant number of colonization cases by the two oral parasites was missed upon using the microscopic approach.…”
Section: Discussionmentioning
confidence: 73%
“…The role of the parasitic fraction of the oral microbiome, namely: Entamoeba gingivalis and Trichomonas tenax, is considered among the proposed models regarding the contributing factors to the development of periodontal disease (32,33). Several studies aimed to investigate parasitic oral colonization among healthy individuals and those with periodontal disease with remarkably variable results (34)(35)(36)(37)(38)(39)(40)(41). Such variability can be related to adoption of different approaches for parasite detection, the existence of previously unknown genetic variants of oral parasites, in addition to limitations of small sample sizes, and possible bias in selection of study subjects among others as reviewed recently (42,43).…”
Section: Introductionmentioning
confidence: 99%